Experimental Study Of Yaw Angle Effect On The Aerodynamic Characteristics Of A Road Vehicle Fitted With A Rear Spoiler - Cheng, See Yuan; Chin, Kwang Yhee; Mansor, Shuhaimi; Abd Rahman, Abd Basid (Elsevier B.V., 2019)
This study investigates the yaw angle effect on the aerodynamic performance of a hatchback model fitted with a roof spoiler. Although the aerodynamic performance of road vehicles is highly dependent on its yaw angle, it has rarely been considered in studies pertaining to roof spoiler applications. Two common types of spoilers are studied, namely, strip and wing types. The hatchback model is based on the Ahmed body at 35' slant angle. The yaw angle affects the aerodynamic performance of the hatchback model negatively regardless of the presence of a spoiler. However, the impact is more pronounced with the absence of a spoiler, particularly at higher yaw angles. Most importantly, the use of a spoiler prevents the bi-stability behaviour of flow which occurred in the model without the spoiler. Furthermore, the strip spoiler reduces both the drag and lift coefficients (Cd and Cl), whereas the wing type results in a greater reduction in Cl while penalising Cd. The results of the surface pressures indicate that the changes in the flow around the rear slanted body are the main factors affecting the aerodynamic performance of the hatchback model using the spoiler.